Optimalisasi Peran Pengawas Sebagai Evaluator Kurikulum (Studi Kasus di MAN Trenggalek) - Kusmalik Kusmalik (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2015)
The curriculum is a core dimension of education determine the style and color of the process and outcomes of education. To be able to design and implement a good curriculum, the necessary synergy of all components of education. Teachers and supervisors are the main actors in the context of curriculum evaluation. Optimizing the role of each through a variety of efforts to increase the competence and empowerment must be done. In addition, the synergy between the two through an atmosphere of mutual respect and provide support to one another becomes important to be able to produce a good curriculum design and educational outcomes as expected by all stakeholders of the education agency.